2007
DOI: 10.1074/jbc.m610925200
|View full text |Cite
|
Sign up to set email alerts
|

NAADP Mobilizes Calcium from the Endoplasmic Reticular Ca2+ Store in T-lymphocytes

Abstract: The target calcium store of nicotinic acid adenine dinucleotide phosphate (NAADP), the most potent endogenous calcium-mobilizing compound known to date, has been proposed to reside in the lysosomal compartment or in the endo/sarcoplasmic reticulum. This study was performed to test the hypothesis of a lysosomal versus an endoplasmic reticular calcium store sensitive to NAADP in T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 36 publications
(51 reference statements)
1
36
0
Order By: Relevance
“…At odds with the notion that NAADP activates a novel channel located on acidic organelles, several reports concluded instead that NAADP mobilized Ca 2+ from the ER through direct activation of ryanodine receptors (Hohenegger et al, 2002; Gerasimenko et al, 2003; Steen et al, 2007). An effect of NAADP on plasma membrane TRPM2 channels was also reported (Beck et al, 2006).…”
Section: Two-pore Channels As Naadp-sensitive Ca2+ Channelsmentioning
confidence: 97%
“…At odds with the notion that NAADP activates a novel channel located on acidic organelles, several reports concluded instead that NAADP mobilized Ca 2+ from the ER through direct activation of ryanodine receptors (Hohenegger et al, 2002; Gerasimenko et al, 2003; Steen et al, 2007). An effect of NAADP on plasma membrane TRPM2 channels was also reported (Beck et al, 2006).…”
Section: Two-pore Channels As Naadp-sensitive Ca2+ Channelsmentioning
confidence: 97%
“…In a number of reports we demonstrated that endogenous NAADP was formed upon stimulation of the T cell receptor (TCR)/CD3 complex (Gasser et al, 2006),RyR are necessary for both global and local Ca 2+ release (Langhorst et al, 2004; Dammermann and Guse 2005), andNAADP evoked Ca 2+ release was not blocked by the V-ATPase inhibitor bafilomycin A1 (Steen et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…NAADP evoked Ca 2+ release was not blocked by the V-ATPase inhibitor bafilomycin A1 (Steen et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In sea urchin eggs, NAADP releases Ca 2ϩ from acidic Ca 2ϩ stores, lysosome-related organelles (20). However, NAADP can also release Ca 2ϩ from the endoplasmic reticulum (21)(22)(23).…”
mentioning
confidence: 99%